INCREASING THE RELIABILITY OF PRECIPITATION FORECASTING SOIL FOUNDATIONS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The analysis of calculation sediment soil foundation a layered method of summation by performed. For increase of accuracy of valuation compressibility of the soil and forecast subsidence proposed a more accurate method of calculating the sediment soil foundation. Keywords: deformation modulus, compressibility, forecasting, porosity coefficient, accuracy.